Dari Ngak-Ngik-Ngok, ke Cengeng, lalu Ambyar: Politik Afektif Musik Indonesia - Fauzanafi, Muhammad Zamzam (Umbara, 2024)
This article examines the relationship between music and politics through the lens of affective resonance, spanning the Soekarno era (ngak-ngik-ngok), the New Order (cengeng), and the Reformation (ambyar) era. Using music analysis and remote ethnography as its methods, the article argues that music, particularly its sonic qualities, plays a crucial role in shaping affective politics—a form of politics distinct from ideological politics. The banning of ngak-ngik-ngok music during the Soekarno era was not merely an anti-imperialism or anti-colonialism ideological stance but also an exercise in affective politics, where Soekarno sought to regulate citizens' "mental health" through sound. Similarly, the prohibition of cengeng songs during the New Order (Orba) era reflected concerns about the interplay between their melancholic sound and lyrical content, which were perceived as weakening the ideology of national development. In contrast, the melancholia of ambyar music in the Reformation era introduces a form of "pleasant sadness," reinforcing apolitical tendencies as a response to the exhaustion caused by global neoliberalism. This affect-ive engagement offers an alternative political expression, shaping sensibilities and moods outside traditional political frameworks. Affects and sensibilities mediated through listening practices and sonorous environments are as influential in shaping political dynamics as institutions, markets, and the information networks of civil society organizations.